The Cu Based AlGaN/GaN Schottky Barrier Diode - 李迪 贾利芳 樊中朝 程哲 王晓东 杨富华 何志 (Chinese physics letters, 2015)
The electrical characteristics of Cu and Ni/Al AlGaN/GaN Schottky barrier diodes on Si su bstrates are compared. The onset voltage of Cu Schottky diodes is about 0.4 V less than the Ni/Al contact. For the Cu/Ni Schottky contact, the leakage current is 4.7 × 10^-7 A/mm at -10 V. After annealing, the leakage current is decreased to 3.7 × 10^-7 A/mm for 400℃ or 4.6 × 10^-8 A/mm for 500℃, respectively. The electrical property is affected by the thickness ratio of Cu to Ni. The Cu/Ni for 80/20 nm shows a low onset voltage, while the Cu/Ni for 20/80 nm shows a low leakage current. Both breakdown voltages are above 720 V.